Influence of cataract surgery on repeatability and measurements of spectral domain optical coherence tomography - Bambo, Maria P; Garcia-Martin, Elena; Otin, Sofia; Sancho, Eva; Fuertes, Isabel; Herrero, Raquel; Satue, Maria; Pablo, Luis (British journal of ophthalmology, 2014)
Backgrounds/aims To evaluate the effect of uncomplicated cataract phacoemulsification on the measurements of macular and retinal nerve fibre layer (RNFL) in healthy subjects using two spectral domain (SD) optical coherence tomography (OCT) instruments—Cirrus OCT (Zeiss) and Spectralis OCT (Heidelberg)—and to assess the reliability of the measurements obtained with these two devices before and after cataract surgery. Methods The study included 60 eyes of 60 healthy subjects (22 men and 38 women, 54–88 years of age) who underwent cataract phacoemulsification. One month before and one month after surgery, three repetitions of scans were performed using the RNFL and macular analysis protocols of the Cirrus and Spectralis OCT instruments. The differences between RNFL and macular thickness measurements obtained in the two visits were analysed. Repeatability was evaluated by calculating the coefficient of variation (COV) for each of the parameters recorded and for each visit. Results The RNFL measurements obtained with the Cirrus and Spectralis OCT differed before and after surgery, and most of these differences were statistically significant (p<0.05). Macular thickness measurements using the Spectralis OCT were not significantly different between the two visits, whereas the differences found with the Cirrus OCT were statistically significant. The repeatability was better after surgical removal of the cataract, and the differences between COV in the two visits were significant with the Cirrus OCT. Conclusions The presence of cataracts affects RNFL and macular measurements performed with SD-OCT. The repeatability of the images significantly improved after cataract phacoemulsification when using the Cirrus OCT.